Chemical, physical, and biological attributes in soils affected by deposition of iron ore tailings from the Fundão Dam failure - Silva, Aline Oliveira; Guimarães, Amanda Azarias; Lopez, Bruna Daniela Ortiz; Zanchi, Carin Sgobi; Vega, Cesar Florentino Puma; Batista, Éder Rodrigues; de Souza Moreira, Fatima Maria; da Costa Souza, Flávia Romam; Pinto, Flávio Araújo; dos Santos, Jessé Valentim; Carneiro, Joana Junqueira; Siqueira, José Oswaldo; et al. (Environmental monitoring and assessment, 2021)
Monitoring degraded areas is essential for evaluation of the quality of the rehabilitation process. In this study, we evaluate how the physical and chemical characteristics of the mixture of iron ore tailings with the soil have affected the soil microbial biomass and activity in areas along the Gualaxo do Norte River after the Fundão Dam disaster. Composite soil samples were collected from areas that were impacted (I) and not impacted (NI) by the tailings. The following attributes were evaluated: chemical element content; soil density, porosity, and texture; microbial biomass carbon; basal respiration; and enzyme activity and density of microbial groups (bacteria, actinobacteria, fungi, arbuscular mycorrhizae, phosphate solubilizers, cellulolytic microorganisms, nitrifiers, ammonifiers, and diazotrophs). According to result, the deposition of tailings increased the pH and the soil available P, Cr, Fe, and Mn content and reduced organic matter. The physical and biological attributes were negatively affected, with increases in the silt content and density of the soil, and reduction in macroporosity and in the microbial biomass and activity of the soil (respiration and enzymes) in the impacted area. However, the impacted areas exhibited greater densities of some microbial groups (cellulolytic microorganisms, nitrifiers, and diazotrophic bacteria). Modifications in the organic matter and silt content are the main attributes associated with deposition of the tailings that affected soil microbial biomass and microbial activity. This may affect erosive conditions and the functionality of the ecosystem, indicating an imbalance in this environment. In contrast, the higher density of some microbial groups in the impacted areas show the high rehabilitation potential of these areas.